A Study of the Incorrect Use of Thai Language in Official Documents: A Case Study of the Academic Division, Chulachomklao Royal Military Academy, 2022 - Khiawnga, Sarisa (CRMA Journal of Humanities and Social Sciences, 2024)
This research aimed to study the incorrect use of the Thai language in 120 official documents collected from the document circulating system of the Academic Division, Chulachomklao Royal Military Academy, between 1 January 2022 and 30 June 2022. The research found that there were three aspects to the incorrect use of the Thai language in official documents, namely: 1) Word choice, 2) Sentence structure, and 3) Writing style. For the word choice, two types of incorrect usage were found, including the usage of wrong vocabulary according to Thai linguistic principles and inappropriate levels of linguistic formality. Errors in sentence structure can be classified into four types: use of linguistically incorrect sentence structure, incomplete sentence structure, connecting sentences by linking repeated words close together, as well as overlong and complex sentences. Lastly, errors in writing style appear in the usage of punctuation and incorrect spacing.